Efforts in improving managerial competency of executing and supervisory position with competency based training method - Gofur Ahmad (Ukrainian Journal of Educational Studies and Information Technology, 2020)
The purpose of this study was to determine whether the learning method through competency based training designed according to the results of the competency gap can improve managerial competencies in cooperation and communication of executing office holders and managerial competencies in self and others development as well as decision-making of the supervisory office holders. The research was conducted in Jakarta in one of government agencies by taking the executing and supervisory officials as research target. The research method used in this study is the method of action research, which among its aims is to find solutions to problems that exist in a particular study area. The results of the study showed that (1) there are significant differences between before and after holding competency based training for executing officials. The average Post-CBT value for executing positions was 3.45 which is higher than the average Pre-CBT value of 1.75. It illustrates that the learning method through competency based training designed according to the results of competency gaps can improve managerial competencies in cooperation and communication of executing office holders, and (2) there are significant differences between before and after holding competency based training for supervisory office holders. The average Post-CBT value for supervisory positions was 3.60 which is higher than the average Pre-CBT value of 1.80 which illustrates that the learning method through competency based training designed based on the results of competency gaps can improve managerial competencies in self and others development as well as decision-making for supervisory office holders.